2012
DOI: 10.3402/rlt.v20i0.14431
|View full text |Cite
|
Sign up to set email alerts
|

The implementation and evaluation of a new learning space: a pilot study

Abstract: A dramatic, pedagogical shift has occurred in recent years in educational environments in higher education, supported largely by the use of ubiquitous technologies. Increasingly, emphasis is being placed on the design of new learning spaces, often referred to as ''Next Generation Learning Spaces'' (NGLS) and their impact on pedagogy. The traditional idea of ''classroom'' now incorporates the use of both physical and virtual space. Increasing availability of digital technologies has enabled access by teachers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 2 publications
3
27
0
1
Order By: Relevance
“…Motivated by the above-mentioned studies, the novelty in this paper is that it is focused on the use of smartphones by the students. As many studies show, the success of web-based learning systems will not be achieved if students fail to use such systems [45]. Both the survey and interview data indicated that students used mobile phones to access Moodle for learning materials much more often than for other uses, which indicates that the use of mobile access to Moodle was still at the lowest level as suggested in [15].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Motivated by the above-mentioned studies, the novelty in this paper is that it is focused on the use of smartphones by the students. As many studies show, the success of web-based learning systems will not be achieved if students fail to use such systems [45]. Both the survey and interview data indicated that students used mobile phones to access Moodle for learning materials much more often than for other uses, which indicates that the use of mobile access to Moodle was still at the lowest level as suggested in [15].…”
Section: Discussionmentioning
confidence: 89%
“…During the years, various attempts to evaluate LMSs and especially Moodle as an effective learning tool have been successfully made. The majority of the studies concluded that LMSs -including Moodle -are inadequate in supporting the level of interaction, personalization, and engagement demanded by the tech-savvy students [4,7,43,45]. In fact, many studies have reported that if we want the LMSs to be used less as electronic document repositories and more as active learning tools it is necessary to provide to the new generations of students that were 'born with smartphones' and are very familiar with the latest technologies the right tools to access the educational content.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations